The Effect of Cash Transfers on Fertility: Evidence from Argentina - Garganta, Santiago (2017)
In 2009 Argentina introduced a large poverty-alleviation program (AUH) that provides monthly cash transfers per child to households without workers in the formal sector. In this paper we study the potential unintended effect of this program on fertility. We apply a difference-in-difference strategy comparing the probability of having a new child among eligible and ineligible mothers both before and after the program inception. The intention to treat estimations suggest a significant positive impact on fertility in households with at least one child (around 2 percentage points), but no significant effect on childless households. Given the short time window since the implementation of the AUH, we are unable to identify whether this positive effect reflects changes in the timing of births or in the equilibrium number of children.